Optimizing Policymakers' Loss Functions in Crisis Prediction: Before, Within or After? - Peter Sarlin; Gregor von Schweinitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
Early-warning models most commonly optimize signaling thresholds on crisis probabilities. The ex-post threshold optimization is based upon a loss function accounting for preferences between forecast errors, but comes with two crucial drawbacks: unstable thresholds in recursive estimations and an in-sample overfit at the expense of out-ofsample performance. We propose two alternatives for threshold setting: (i) including preferences in the estimation itself and (ii) setting thresholds ex-ante according to preferences only. We provide simulated and real-world evidence that this simplification results in stable thresholds and improves out-of-sample performance. Our solution is not restricted to binary-choice models, but directly transferable to the signaling approach and all probabilistic early-warning models.
urn:nbn:de:gbv:3:2-48552
Keywords: C35; C53; G01; 330; early-warning models; loss functions; threshold setting; predictive performance